The mutations induced by oxidatively damaged nucleotides, 5-formyl-dUTP and 5-hydroxy-dCTP,in Escherichia coli. - Fujikawa, K (1998)
The mutational properties of 5-formyl-2'-deoxyuridine 5'-triphosphate (5-CHO-dUTP) and 5-hydroxy-2'-deoxycytidine 5'-triphosphate (5-OH-dCTP), the major oxidatively damaged pyrimidine nucleotides derived from dTTP and dCTP, respectively, were analyzed by an in vivo assay. 5-CHO-dUTP and 5-OH-dCTP were directly incorporated into Escherichia coli , and their mutagenicities were evaluated by the chromosomal lacI forward mutation assay. The mutation frequencies increased, depending on the dose of these damaged nucleotides, indicating that these nucleotides were incorporated into E.coli and acted as mutagens in vivo . The mutagenicities of 5-CHO-dUTP and 5-OH-dCTP were comparable to that of 8-hydroxy-2'-deoxyguanosine 5'-triphosphate, a major form of dGTP oxidative damage. 5-CHO-dUTP induced G.C to A.T, A.T to G.C and G.C to T.A mutations, and 5-OH-dCTP elicited G.C to A.T, A.T to C.G and G.C to T.A mutations.